Amending America's unwritten Constitution / edited by Richard Albert, Ryan C. Williams, Yaniv Roznai. - Albert, Richard (Law professor); Roznai, Yaniv; Williams, Ryan C., 1975- (Comparative constitutional law and policy., 2022)
It is well known that the US Constitution has been amended twenty-seven times since its creation in 1787, but that number does not reflect the true extent of constitutional change in America. Although the Constitution is globally recognized as a written text, it consists also of unwritten rules and principles that are just as important, such as precedents, customs, traditions, norms, presuppositions, and more. These, too, have been amended, but how does that process work? In this book, leading scholars of law, history, philosophy, and political science consider the many theoretical, conceptual, and practical dimensions of what it means to amend America's 'unwritten Constitution': how to change the rules, who may legitimately do it, why leaders may find it politically expedient to enact written instead of unwritten amendments, and whether anything is lost by changing the constitution without a codified constitutional amendment.